(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Spondylolisthesis is described as a translation of a vertebra with respect to the vertebra below without any modification or notable lesion to the pars interarticularis. Lumbar spondylolisthesis can be considered as various conditions like Kati shoola, Kati Graha, Trika Graha, Prushta Graha, Trika Shoola, Prushta Shoola, Grudrasi in Ayurveda. The present article deals with a case of diagnosed Grade 1 lumbar spondylolisthesis of L4 over L5 and got advised for surgery. The Ayurvedic diagnosis of Kati soola was made. Management included Abhyanga, Kativasti, Kshira vasti, Virechana, Vaitarana vasti and Chincha lavana sweda along with internal medications. Chincha lavana sweda is a very simple and effective Swedana procedure to cure pain in low back, especially due to Spondylolisthesis. But it is not widely used. This case report also wants to introduce the technique to Ayurvedic practitioners who are unaware of it. Before treatment, total score on Oswestry low back pain disability questionnaire was 34 (68%) and at the time of discharge, the score was 8 (16%). On Roland-Morris low back pain and disability questionnaire, the before treatment score was 17 and at the time of discharge it was reduced to 4. That means the patient showed an improvement of 76% on Roland-Morris low back pain and disability questionnaire. The present case report substantiates effectiveness of classical Ayurvedic Management in spondylolosthesis.